Virtues and relativism. Alisdair MacIntyre’s attempt to overcome relativism. (Diametros, 2004)
The article considers Alisdair MacIntyre’s suggestion for overcoming relativism. MacIntyre believes that contemporary moral debates (between the three principal philosophical traditions, Thomism, Postnietzschean philosophy, and the liberal tradition) are characterized by an “incommensurability and incommunicability of positions” and are therefore necessarily inconclusive. In spite of this relativistic point of departure, MacIntyre attempts to show how it is nevertheless possible to carry on a rational debate among such radically different philosophical traditions. He points out that thanks to the conception of virtue developed by him (based upon his earlier conceptions of narrative personality, tradition, and practice), the ethics of virtue is the most viable alternative. It provides the conceptual apparatus necessary to overcome the problems that plague other philosophical traditions. Since the current version of the ethics of the virtues is a part of Thomism, MacIntyre points to the latter as the intellectually most satisfying option. The article closes with a discussion of various objections raised against MacIntyre’s conception.